Guest editorial. Issue 3 (1st December 2019) - Infante Mora, Eva; Greenwood, Davydd J.; Ivanchikova, Melina
Abstract : This special issue is devoted to a study of an action research-based reform of a US university study abroad programme to make it a genuine intercultural immersion experience. The four-year collaborative reform process combined participatory organisational redesign, the development of a comprehensive active learning approach and the teaching of intercultural competence through ethnographic immersion and community engagement in Seville, Spain. The case is an example of the development of intercultural competencies through guided behavioural change, of action research to reform higher education programmes and of active learning combined with formative and summative evaluation. The reader will learn about the experiences of the staff, faculty and mentors in the Consortium for Advanced Studies Abroad (CASA)-Sevilla study abroad programme and those of the sponsoring US universities as they together achieved a fundamental reform of a decades-old study abroad immersion programme. This special issue has many authors because this was a collaborative action-research project with continuous group work and brainstorming. The authors' names are placed in the sections where the authorship is clear, but, as befits a collaboration, many of the ideas are the result of the combined thinking of all the authors. Authorship of the various sections has been allocated mainly to clarify for readers the most relevant author to contact to learn more about particular dimensions of the process. The guest editors took on the editorial duties on behalf of this larger group.